Evaluating forecasting method using autoregressive integrated moving average (ARIMA) approach for shariah compliant oil and gas sector in Malaysia / Nashirah Abu Bakar, Sofian Rosbi and Kiyotaka Uzaki - Abu Bakar, Nashirah; Sofian, Rosbi; Uzaki, Kiyotaka (Unit Penerbitan UiTM Kelantan, 2016)
Stock market is one of the most important indicators about the status of the economic for a country. Positive increment of dynamic movement for the share price indicates good performance of stock market in Malaysia. This paper investigates the reliability of ARIMA statistical method to forecast the share price performance for oil and gas sector in Malaysia Stock Exchange. In this research, one shariah-compliant company was selected, namely Sapura Energy Berhad. This company is one of the oil and gas companies that issued Initial Public Offerings (IPO) in year of 2012. In ex-post analysis, the forecasting model shows the Autoregressive Integrated Moving Average (ARIMA) (1, 1, 1) contributes 3.752% error between forecast value and actual value. Therefore, the results conclude that the performance of Sapura Energy Berhad can be forecast accurately using ARIMA model of (1, 1, 1). The value in February 2018 is forecasted as MYR 1.387169 for every share of Sapura Energy Berhad. The findings of this study will help investors to evaluate and forecast the performance of oil and gas sector in Malaysia. In addition, this study will help investors to manage and make their investment decision to increase profit and reduce the loss in investment. Furthermore, the findings from this study will help economists to evaluate the current economic condition of oil and gas in Malaysia. Then, preventive action can be implement to secure a good level of economic condition in Malaysia.